Characterization of native Bacillus thuringiensis strains against Spodoptera litura and Spodoptera exigua - SARKAR, SOURAV; KALIA, VINAY K (The Indian Journal of Agricultural Sciences, 2022)
In the present study 12 native Bt strains isolated from insect cadavers were screened for their bioefficacy against neonates of economically important polyphagous pests Spodoptera litura and Spodoptera exigua by feeding assays at single concentrations of 10 Î¼g/g of diet. Toxicity of Bt strains against neonates of S. litura and S. exigua varies from 39.04% (VKK-EV and VKK-PX2) to 70.97% (VKK-AC1) and 20.0% (VKK-AC1 and VKK-MPS) to 88.00% (VKK-AC2) on 7th day after treatment respectively. The LC50 values for potential Bt strains against S. litura varied from 0.87 Î¼g/gm (VKK-AC1) to 9.36 Î¼g/gm (VKK-AG2) while, against S. exigua ranged from 1.00 Î¼g/g (VKKAC2) to 13.95 Î¼g/g (VKK-SO) of diet. Gene profiling of potential Bt strains revealed the presence of cry1A, cry1D, cry1I, and cry2 gene. Further studies on characterization of these novel cry genes from potential native Bt strains will be valuable for management of Spodoptera spp.